Identifying eye blinks in EEG signal analysis - Sovierzoski, M.A.; Argoud, F.I.M.; de Azevedo, F.M. (2008 International Conference on Information Technology and Applications in Biomedicine, 2008)
The electroencephalogram is a noninvasive record of the brain activity using electrodes placed on the scalp. The electroencephalographic signal can be contaminated by other signal sources, called artifacts. Among the several artifact sources, eye blink is one of the main sources of interference in the EEG exam, and can be erroneously interpreted as epileptiform activity. This study analyzed eye blink signals acquired by EEG electrodes. The main objective of this study was to develop a neural network classifier specialized in the identification of eye blinks in EEG signals. The statistical study of the eye blinks in EEG signals, the methodology and the results of the identification of this event are presented.